(untitled) (Perner’s Contacts, 2011)
There is described a method of the verification of a given tariff. This method is based on the principle of a simulation of some parcel shipping service operation. The missing data about transport demand are generated randomly such a way that the distribution of the demands in time and space is close to reality. The suboptimal vehicle routes are then created on the basis of generated transport demand. The authors used their own proprietary software to create these routes. The running costs are then computed according to these routes together with the revenue from sales. It is possible to estimate the profitability of the service based on given tariff (if the other costs are also known).